2009
DOI: 10.1186/1550-2783-6-16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 28 days of resistance exercise and consuming a commercially available pre-workout supplement, NO-Shotgun®, on body composition, muscle strength and mass, markers of satellite cell activation, and clinical safety markers in males

Abstract: PurposeThis study determined the effects of 28 days of heavy resistance exercise combined with the nutritional supplement, NO-Shotgun®, on body composition, muscle strength and mass, markers of satellite cell activation, and clinical safety markers.MethodsEighteen non-resistance-trained males participated in a resistance training program (3 × 10-RM) 4 times/wk for 28 days while also ingesting 27 g/day of placebo (PL) or NO-Shotgun® (NO) 30 min prior to exercise. Data were analyzed with separate 2 × 2 ANOVA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
54
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 57 publications
10
54
3
Order By: Relevance
“…However, as far as we know, most multi-ingredient supplementation used in resistance training studies contain creatine (Beck et al, 2007; Kraemer et al, 2007; Schmitz et al, 2010; Shelmadine et al, 2009). There is strong support that creatine supplementation during resistance training is more effective in enhancing training specific task for strength and strength-endurance than resistance training alone (Rawson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, as far as we know, most multi-ingredient supplementation used in resistance training studies contain creatine (Beck et al, 2007; Kraemer et al, 2007; Schmitz et al, 2010; Shelmadine et al, 2009). There is strong support that creatine supplementation during resistance training is more effective in enhancing training specific task for strength and strength-endurance than resistance training alone (Rawson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Two primary cellular processes are involved with hypertrophy responses in mammalian skeletal muscle. The first process involves both pre-and posttranslational mechanisms that result in the accretion of myofibrillar protein and subsequent myofiber enlargement due to increases in the myonuclear domain (Bickel et al 2005;Shelmadine et al 2009). The second process results in myofiber enlargenment due to a decreased myonuclear domain resulting from activation and proliferation of myogenic satellite cells which fuse into muscle fibers, thereby providing additional myonuclei for augmented transcriptional activity and subsequent protein synthesis (Han et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, studies have demonstrated the efficacy of CRE supplementation when mixed into caffeinated tea or COF (4, 9). Because many pre-workout supplement formulations include both CRE and CAF (15, 28, 33), further research on the potential interaction is needed. While previous studies on CRE+CAF supplementation have employed unique exercise tests consisting of electrical stimulation (19) or isokinetic knee extension (17, 38), the current study used dynamic exercise tests relating more closely to the training of many resistance trained individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported performance improvements from CRE mixed into caffeinated tea or coffee (COF) (4, 9), and a number of multi-ingredient supplements containing CRE+CAF, among other ingredients, have been shown to improve outcomes for strength, power, and body composition (15, 28, 33). Research has also indicated that acute CAF supplementation (a single dose, consumed 60 min prior to an exercise bout) after CRE loading may improve performance more than CRE loading alone (24, 25).…”
Section: Introductionmentioning
confidence: 99%